SELENDANG LURIK: LAMBANG KEPERKASAAN PEREMPUAN-PEREMPUAN DUSUN NITEN, KELURAHAN POGUNG, KECAMATAN CAWAS, KLATEN (SEBUAH KAJIAN ESTETIKA) - Damar Tri Afrianto (Institut Seni Indonesia Surakarta, 2014)
Lurik scarves manifests in a functional artifacts that have values , ideas, and spirit for the Java communityagriculture. In Niten hamlet, village Pogung, sub Cawas, Klaten district, was found five craftsmen who producekinds of lurik scarves. This striped shawl users generally are women and function as equipment of their work,such as carrying herbs, lifting firewood, and bringing lunch to go to the field . Regardless of the functionalproperties, this study aims to find meaning and values contained in striated shawl . Discussion of lurik, thereare three aspects that characterize the embodiment of a lurik: pattern, style and meaning. Pattern, style andmeaning is represented in the composition of coherent lines. Through pattern, vertical lines and horizontallines, read a notion and meaning contained in lurik shawl . This study uses the concept of aesthetic JakobSumardjo use of “ a pattern of three “ to analyze the form of lurik . Study concept of aesthetics of the lineswhich manifests in the form of merging shawl striated vertical and horizontal lines. This shows the meaning ofefforts to balance the heavenly (vertical) and temporal (horizontal). Vertical and horizontal harmony producestranscendent paradox. Harmonization between vertical lines and horizontal in striated shawl implied a desire,purpose, hope, hard work, especially women in the village Pogung Niten to achieve a perfect life.Keywords : scarves, lurik, aesthetics